A novel dual GLP-1 and GIP incretin receptor agonist is neuroprotective in a mouse model of Parkinson's disease by reducing chronic inflammation in the brain. Issue 6 (13th April 2016) - Cao, Lijun; Li, Dongfang; Feng, Peng; Li, Lin; Xue, Guo-Fang; Li, Guanglai; Hölscher, Christian
Abstract : The incretins glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are growth factors. GLP-1 mimetics are on the market as treatments for type 2 diabetes. Both GLP-1 and GIP mimetics have shown neuroprotective properties in previous studies. In addition, the GLP-1 mimetic exendin-4 has shown protective effects in a clinical trial in Parkinson's disease (PD) patients. Novel GLP-1/GIP dual-agonist peptides have been developed to treat diabetes. Here, we report the neuroprotective effects of a novel dual agonist (DA-JC1) in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) mouse model of PD. MPTP was injected once daily (20 mg/kg intraperitoneally) for 7 days and the dual agonist was coinjected once daily (50 nmol/kg intraperitoneally). We found that the drug reduced most of the MPTP-induced motor impairments in the rotarod, open-field locomotion, and muscle strength test. The number of tyrosine hydroxylase-positive neurons in the substantia nigra and striatum was reduced by MPTP and increased by DA-JC1. Synapse numbers (synaptophysin expression) were reduced in the substantia nigra and the striatum by MPTP and DA-JC1 reversed this effect. The activation of a chronic inflammation response by MPTP was considerably reduced by the dual agonist (DA) (astroglia and microglia activation). Therefore, dual agonists show promise as a novel treatment of PD.